Hubungan Obesitas dengan Body Dissatisfaction pada Mahasiswa Fakultas Kedokteran Universitas Islam Bandung - Deandra Chitraenrieta Ramdhanoviella; Prawiradilaga, Rizky Suganda; Surialaga, Samsudin (UNISBA Press, 2024)
Abstract. The problem of obesity is a health problem that is growing globally in both developed and developing countries. Obesity can cause many health problems, including psychological problems, one of which is body dissatisfaction. This study aims to assess body dissatisfaction and analyze the relationship between obesity and body dissatisfaction in students who are obese at the Faculty of Medicine, Bandung Islamic University. This research uses quantitative analytical methods with a cross-sectional approach. The research subjects were 60 people taken using purposive sampling technique. Subjects were allocated into 2 groups, namely 30 people with obese Body Mass Index (BMI) and 30 people with normal BMI). Statistical analysis used SPSS version 26 software. The Spearman correlation test was used in this study to analyze the correlation between obesity and body dissatisfaction scores. The research results show that there is a significant relationship (p-value=0.012) between obesity and body dissatisfaction with a positive correlation with low correlation strength (r=0.321). It is hoped that someone will pay more attention to physical activity and diet so as not to become obese which can increase body dissatisfaction. Abstrak. Obesitas menjadi masalah kesehatan yang berkembang secara global baik di negara yang maju maupun negara berkembang. Obesitas dapat mengakibatkan banyak masalah pada kesehatan termasuk masalah psikologis salah satunya body dissatisfaction. Penelitian ini bertujuan untuk menilai body dissatisfaction dan menganalisis hubungan antara obesitas dengan body dissatisfaction pada dewasa muda yang mengalami obesitas. Penelitian ini menggunakan metode analitik kuantitatif dengan pendekatan cross-sectional. Subjek penelitian berjumlah 60 orang diambil dengan teknik purposive sampling. Subjek dialokasikan kedalam 2 kelompok yaitu 30 orang dengan Indeks Massa Tubuh (IMT) obesitas dan 30 orang dengan IMT normal. Analisis statistik menggunakan software SPSS versi 26. Uji korelasi Spearman digunakan pada penelitian ini untuk menganalisis korelasi antara obesitas dengan skor body dissatisfaction. Hasil penelitian menunjukan adanya hubungan yang signifikan (p-value=0.012) antara obesitas dengan body dissatisfaction dengan korelasi positif dengan kekuatan korelasi rendah (r=0,321). Dari hasil tersebut, diharapkan seseorang lebih memperhatikan aktivitas fisik dan pola makan agar tidak mengalami obesitas yang dapat meningkatkan body dissatisfaction.